Financial Control Therapy in the Eradication of Undeclared Work and Tax Evasion - Nitu, Alin Sergiu; Constantin, Marcel (Acta Universitatis Danubius. Œconomica, 2022)
As forms of the black economy, undeclared work and tax evasion are topical issues that are the subject of governmental and non-governmental policies both nationally and internationally, treated from various angles and in the literature, because it has important implications and ramifications in the budget balance. and implicitly in everyday social life. The underground economy, which is mainly a feature of the market economy, is based on freedom not necessarily misunderstood but deliberately understood according to the pecuniary interest of actors operating in this type of undeclared economy, most often through well-behaved economic agents. fiscal and commercial that contravenes the rules of law, freedom that must be controlled in terms of the legality of activities. As a result, financial control through the forms and bodies that carry it out is very important, perhaps not in eradicating them as they should be, but at least in diminishing them.